Discovery of two new species of Alucitidae (Lepidoptera) from Vietnam - Byun, Bong-Kyu; Park, Kyu-Tek (Zootaxa, 2007)
Two new species of Alucitidae, Pterotopteryx nigrifasciata sp. nov. and P. vietana sp. nov., are described from Vietnam. Photographs of the facies and genitalia are presented.